Analysis of mechanical properties on API 5CT pipe casing welded using GTAW- SMAW process - Syukran, Syukran; Azwinur, Azwinur; Fachrurrazi, Fachrurrazi (Politeknik Negeri Lhokseumawe, 2024)
The drilling process commonly employs API 5CT pipes, one type of which is API 5CT Casing Pipe Grade L80 Type-1. Long casing pipes are generally connected using the Threaded and Coupled (male-female) method. In certain conditions, welding is used for joining, and the combination welding process GTAW-SMAW is commonly employed in the field. The electrodes used are generally ER-70S-G (GTAW) and E7010-P1 (SMAW). The E7010-P1 electrode is difficult to obtain in the field. It is not only expensive but also scarce. Therefore, in some cases, construction contractors often substitute the E7010-P1 electrode with E7016, which is more readily available. This substitution is based on the consideration that both electrodes have similar tensile strength values (70ksi). This study aims to determine the mechanical properties of the joint process of API 5CT Casing Pipe Grade L80 Type-1 using E7016 electrodes and to evaluate the feasibility of substituting it for the E7010-P1 electrode. NDT testing was performed using a penetrant test, while DT testing was carried out using Vickers Hardness testing. The hardness test results showed that the highest average hardness value was found in the material using the E7016 electrode, which was 304 HVN, specifically in the weld metal area. Based on these results, E7016 can be recommended as a substitute for the E7010-P1 electrode.